2013
DOI: 10.1371/journal.pone.0059752
|View full text |Cite
|
Sign up to set email alerts
|

Elevated PLA2G7 Gene Promoter Methylation as a Gender-Specific Marker of Aging Increases the Risk of Coronary Heart Disease in Females

Abstract: PLA2G7 gene product is a secreted enzyme whose activity is associated with coronary heart disease (CHD). The goal of our study is to investigate the contribution of PLA2G7 promoter DNA methylation to the risk of CHD. Using the bisulphite pyrosequencing technology, PLA2G7 methylation was measured among 36 CHD cases and 36 well-matched controls. Our results indicated that there was a significant association between PLA2G7 methylation and CHD (adjusted P = 0.025). Significant gender-specific correlation was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 51 publications
2
61
0
1
Order By: Relevance
“…70 A follow-up candidate gene study with TNNT1 found that in individuals without familial hypercholesterolemia, increased methylation was associated with CAD. 71 In other candidate gene studies, increased methylation at CDKN2B was associated with CAD, 72 increased methylation at PLA2G7 was associated with CAD among women, 73 and increased methylation at INS and GNASAS, loci with a methylation status thought to be influenced by the prenatal environment, was associated with increased incidence of MI among women. 74 Although all of these findings are intriguing, for the most part, they have emerged from small sample sizes and need to be replicated in independent cohorts to establish their validity.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 88%
“…70 A follow-up candidate gene study with TNNT1 found that in individuals without familial hypercholesterolemia, increased methylation was associated with CAD. 71 In other candidate gene studies, increased methylation at CDKN2B was associated with CAD, 72 increased methylation at PLA2G7 was associated with CAD among women, 73 and increased methylation at INS and GNASAS, loci with a methylation status thought to be influenced by the prenatal environment, was associated with increased incidence of MI among women. 74 Although all of these findings are intriguing, for the most part, they have emerged from small sample sizes and need to be replicated in independent cohorts to establish their validity.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 88%
“…In certain types of human tissue, positive correlation between gene-body methylation and gene expression has been identified (34,35). Gene-body methylation was reported to be significant in regulating cell context-specific alternative promoters in human and mouse tissues (28).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma levels of cholesterol, triglyceride (TG), alanine transaminase (ALT), aspartate transaminase, uric acid and glucose concentrations were enzymatically measured using a CX7 biochemical analyzer (Beckman Coulter, Brea, CA, USA). DNA methylation was measured using sodium bisulphite DNA conversion coupled with pyrosequencing (28). Briefly, genomic DNA was chemically modified by sodium bisulphite (EpiTech Bisulphite kit; Qiagen, Hilden, Germany) to convert all the unmethylated cytosines into uracils, while the methylated cytosines remained unchanged.…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, a fragment that contains only five CpG sites in the DRD4 promoter was tested in the present study and this fragment may not be sufficient to reflect the DNA methylation state of the whole gene. Thirdly, tissue specificity between the peripheral blood and brain still needs to be taken into account, although a strong correlation of gene methylation between the blood and brain has previously been observed (36). Lastly, a functional study of the target sequence on the RNA and the protein expression levels was not performed due to a lack of samples.…”
Section: P-value Subgroups ------------------------------------------mentioning
confidence: 99%